2016
DOI: 10.1002/ejic.201501304
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin‐Phosphine‐Based Smart Probes for Tracking Biologically Relevant Metal Complexes: From Theoretical to Biological Investigations

Abstract: International audienceTen metal-based complexes and associated ligands have been synthesized and characterized. One of the metal ligands is a coumarin-phosphine derivative, which displays tunable fluorescence properties. The fluorescence is quenched in the case of the free ligand and ruthenium and osmium complexes, whereas it is strong for the gold complexes and phosphonium derivatives. These trends were rationalized by theoretical calculations, which revealed non-radiative channels involving a dark state for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…Despite their good commercial availability and relatively simple chemistry for their incorporation into metal complexes, their photophysical properties are not always ideal for bioimaging purposes, for which tissue light penetration is a handicap. Moreover, depending on the coupling of metallic drug with the fluorophore, the emission of the final complexes could be quenched either through a photoinduced electron transfer or by de‐excitation of the triplet excited state . Figure shows some examples of different metallodrugs tethered with organic chromophores, which are the luminophores most studied so far…”
Section: Optical Theranostic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their good commercial availability and relatively simple chemistry for their incorporation into metal complexes, their photophysical properties are not always ideal for bioimaging purposes, for which tissue light penetration is a handicap. Moreover, depending on the coupling of metallic drug with the fluorophore, the emission of the final complexes could be quenched either through a photoinduced electron transfer or by de‐excitation of the triplet excited state . Figure shows some examples of different metallodrugs tethered with organic chromophores, which are the luminophores most studied so far…”
Section: Optical Theranostic Agentsmentioning
confidence: 99%
“…Organic fluorophores, such as acridine, anthracene, naphthalimide,c oumarine and BODIPY,h ave been traditionally used as opticalp robes for the development of trackable therapeutic agents.D espite their good commercial availability and relatively simple chemistry for their incorporation into metal complexes,t heir photophysical properties are not alwaysi deal for bioimaging purposes, for which tissuel ight penetration is a handicap.M oreover, depending on the coupling of metallic drug with the fluorophore, the emission of the final complexes could be quenched either through ap hotoinduced electron transfer or byd e-excitation of the triplet exciteds tate. [29] Figure 6s hows some examples of different metallodrugs tethered with organic chromophores, which are the luminophores most studied so far. [30] From our perspective,d esigning drugs formed by two metallic fragments that are able to bring together emissivea nd therapeutic properties might result in as martera pproach that could be at urning point.…”
Section: Metallic Drugsmentioning
confidence: 99%
“…To shed light into the process that can turn 1 O 2 photosensitization off by intramolecular PET, qualitative analysis recently applied on several systems to explain the quenching of fluorescence was performed, as well as analysis of electron density changes. The computational approach consists of characterizing the potential‐energy surfaces (PESs) of the low‐lying excited states (S 1 and S 2 ) by means of the TD‐DFT method.…”
Section: Resultsmentioning
confidence: 99%
“…However, their high lipophilicity is not well suited for imaging poorly water‐soluble molecules, such as caffeine derivatives. Consequently, we moved to coumarin, which also gave us very good results in the past (we developed a highly fluorescent family of coumarin‐based gold(I) complexes, which displayed interesting anti‐proliferative properties on several cancer cell lines; moreover, one of them displayed very low toxicity on both zebrafish larvae and mice) . Several studies reported on the anti‐inflammatory effects of coumarin derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…Trommenschlager in-based gold(I) complexes, which displayed interesting antiproliferative properties on several cancerc ell lines;m oreover, one of them displayed very low toxicityo nb oth zebrafish larvae and mice). [16,20,21] Several studies reported on the anti-inflammatory effects of coumarin derivatives. [22][23][24][25] Thus, the coumarin moiety may be more than just af luorescent probe.C onvinced of the high potential of this approach, we designed a family of gold complexes to investigate the impact on their biological properties of caffeineversus benzimidazole scaffolds, the presenceo ft he coumarin probe, and the position of the probe on the caffeine scaffold (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%